COVID-19-associated ischaemic stroke despite use of anticoagulation. Issue 7 (29th July 2021) - Sharma, Shyam; Wood, Michael; Gulli, Giosue
Abstract : A 64-year-old female nurse was admitted to hospital following fever, cough, shortness of breath and low blood pressure. She tested positive for COVID-19 and was treated on a high-dependency unit and prescribed enoxaparin, a prophylactic anticoagulant. Eight days later, she suffered a left middle cerebral artery ischaemic stroke. Over the next 2 weeks, her condition fluctuated, eventually leading to her death. We report her case from clinical history to investigations and outcomes, and explore the potential link between coronavirus, the use of anticoagulation and ischaemic stroke.